Complete Genome Sequences of Four European Subtype Strains of Tick-Borne Encephalitis Virus from Eastern Siberia, Russia - Adelshin, Renat V. (Genome Announc, 2015)
Three tick-borne encephalitis virus (TBEV) strains were isolated from Ixodes persulcatus ticks, and one was isolated from a shrew in the territory of eastern Siberia (Russia). The level of sequence identity compared to Neudoerfl (the European prototype strain) is 97.2 to 97.3%.